As influências do PNAIC na dinâmica do processo de alfabetização - Munhoz Santiago, Luciane Teresinha (2015)
The purpose of this study is to reflect on the effects of PNAIC – National Program for literacy in the Appropriate Age – on teachers’ personal and professional growth, and it is focused on teachers’ educational practice. It is part of a Post-graduation in Education Program from UniLaSalle University, and refers to an investigation on first grade elementary school teacher’s pedagogical literacy process dynamics. This analysis is grounded on a qualitative method of research.Teachers’ feedback on their participation while taking part in PNAIC, as part of the municipal educational system from the city of Porto Alegre, were analysed. PNAIC regards to a teachers’ development program designed for their personal and professional growth while involved in the literacy program. In order to enable first grade teachers to provide a higher level of teaching to their 6-year-old pupils it was necessary to reflect on their interviews and observe their lessons. Through the analyses of teachers’ feedback it was possible to design new routes and possibilities to guide these teachers throughout their process of leading their 6-year-old students in their reading-writing and literacy process. Our attempt was to point out possible changes occurred throughout the educational process towards a qualified education as an outcome of the teachers’ educational program provided by PNAIC. Teachers’ feedback showed their commitment to raise the level of their teaching practices in their 6-year- old groups.During the analysis it was possible to identify important data full of pedagogical input and a universe of pedagogical practices in conformity with the teacher educational program. We have seen a wide repertoire of successful pedagogical practices.